THE NEED FOR ECONOMIC SECURITY OF TERRITORIES AND ITS IMPLEMENTATION USING MARKETING TOOLS - T. D. Maslova; M. V. Chigir (Дискурс)
The heterogeneity of the economic space of the Russian Federation in key indicators of economic development of the territories is discussed. Theoretical and methodological aspects of economic security of territories in clarifying conceptual framework and allocation of the regional dimension of the study of economic security are considered. Special attention is paid to the depressive regions, posing a threat to the economic security of the Russian Federation. The methods, models, indicators, criteria for identification of depressive regions are discussed. The regions related to depressive determined in the result of study of 60 regions within eight federal districts are shown; assessment of their investment potential and its rational use of marketing tool is performed and confirmed by examples.